2007
DOI: 10.1016/j.carres.2007.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and physicochemical characterization of Sargassum vulgare alginate from Brazil

Abstract: Alginate fractions from Sargassum vulgare brown seaweed were characterized by (1)H NMR and fluorescence spectroscopy and by rheological measurements. The alginate extraction conditions were investigated. In order to carry out the structural and physicochemical characterization, samples extracted for 1 and 5h at 60 degrees C were further purified by re-precipitation with ethanol and denoted as SVLV (S. vulgare low viscosity) and SVHV (S. vulgare high viscosity), respectively. The M/G ratio values for SVLV and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
88
0
8

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(108 citation statements)
references
References 39 publications
(20 reference statements)
12
88
0
8
Order By: Relevance
“…The average alginate yield from 5 extractions was 16.4 ± 1.4%, which compares favourably to yields of 16.9% reported for S. vulgare (Torres et al 2007) and of 21.1 to 24.5% for S. fluitans and 16.3 to 20.5% for S. oligocystum (Davis et al 2004). Somewhat higher alginate yields have been reported for S. fluitans (45%) and S. oligocystum (37%) (Davis et al 2003), and for other seaweed species quite varied yields of 3.3% for S. dentifolium, 12.4% for S. asperifolium and 17.7% for S. latifolium have been reported (Larsen et al 2003), suggesting that both species and extraction methods influence yields.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…The average alginate yield from 5 extractions was 16.4 ± 1.4%, which compares favourably to yields of 16.9% reported for S. vulgare (Torres et al 2007) and of 21.1 to 24.5% for S. fluitans and 16.3 to 20.5% for S. oligocystum (Davis et al 2004). Somewhat higher alginate yields have been reported for S. fluitans (45%) and S. oligocystum (37%) (Davis et al 2003), and for other seaweed species quite varied yields of 3.3% for S. dentifolium, 12.4% for S. asperifolium and 17.7% for S. latifolium have been reported (Larsen et al 2003), suggesting that both species and extraction methods influence yields.…”
Section: Discussionsupporting
confidence: 53%
“…Protein, carbohydrate, lipid, fucose, total ash, acid-insoluble ash, water-soluble ash and sulphate contents of the sodium alginate extracts were also measured. Protein content (5.2%) was somewhat higher than low-viscosity (LV, 1.1%) and high-viscosity (HV, 1.0%) alginates extracted from S. vulgare (Torres et al 2007), but their moisture (14 and 16%) and total ash contents (2 and 1%) were comparable with the moisture (16%) and total ash (1.9%) contents of alginate powder prepared here from S. wightii, respectively. With regard to total carbohydrate (46.1%) and fucose (29.2%) contents determined for the S. wightii alginate, these varied considerably from those identified in alginates extracted from various algae harvested from the Egyptian Red Sea coast including Cystoseira trinode (74.9 and 11.6%, respectively), S. dentifolium (57.9 and 5.6%), S. asperifolium (32.2 and 4.2%) and S. latifolium (42.3 and 8.2%) (Larsen et al 2003).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The mixture was stored for 2 hours in a refrigerator to separate the mucilage. The mucilage was separated by centrifugation at 4000 g for 20 minutes at 15 °C and then dried in an oven at 60 °C until a constant weight was reached (Torres et al, 2007). The raw yield was calculated as the ratio of the cyanobacteria dry biomass to the dry weight of the mucilage.…”
Section: Methodsmentioning
confidence: 99%
“…Inversely, more flexible gels may form due to the high amount of alginate-M blocks [29,30]. Some studies also reported that the presence of homopolymeric block structure, namely mannuronic acid blocks (FMM), guluronic acid blocks (FGG) and alternating blocks (FMG) can influence gelling properties of alginate too [31].…”
Section: Chemical Propertiesmentioning
confidence: 99%